2021
DOI: 10.3390/ijerph18041690
|View full text |Cite
|
Sign up to set email alerts
|

Worker Perspectives on Incorporating Artificial Intelligence into Office Workspaces: Implications for the Future of Office Work

Abstract: Workplace environments have a significant impact on worker performance, health, and well-being. With machine learning capabilities, artificial intelligence (AI) can be developed to automate individualized adjustments to work environments (e.g., lighting, temperature) and to facilitate healthier worker behaviors (e.g., posture). Worker perspectives on incorporating AI into office workspaces are largely unexplored. Thus, the purpose of this study was to explore office workers’ views on including AI in their offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Fukumura and colleagues [27] collect worker perspectives on incorporating artificial intelligence (AI) in office settings using a qualitative study design. Based on their findings, the authors note that acceptability of AI in the workplace is complex, that divergent worker-level needs must be addressed, and that AI acceptance is dependent upon whether advantages outweigh challenges.…”
Section: Mixed Methods and Qualitative Methods Approachesmentioning
confidence: 99%
“…Fukumura and colleagues [27] collect worker perspectives on incorporating artificial intelligence (AI) in office settings using a qualitative study design. Based on their findings, the authors note that acceptability of AI in the workplace is complex, that divergent worker-level needs must be addressed, and that AI acceptance is dependent upon whether advantages outweigh challenges.…”
Section: Mixed Methods and Qualitative Methods Approachesmentioning
confidence: 99%
“…Surveillance and control: algorithmic management raises obvious issues of privacy (Bhave et al 2020;Ebert et al 2021;Fukumura et al 2021;Tsamados et al 2022), not just at the workplace, but also at home, notably following the pandemic-induced shift to home-based working (Collins 2020). Privacy infringements can occur at all stages of the data cycle: at the time of collection, in the analysis of the data, in the use of the data, and when data ought to be erased.…”
Section: Algorithmic Managementmentioning
confidence: 99%
“…A real-world evaluation showed that sharing the control between the smart desk and the user to control the thermal environment led to higher satisfaction than in manually controlled environments 20 , opening an avenue for collaborative control and trust between a building and its occupants. In addition to collaboration in making changes, a user-centered approach using focus groups has highlighted numerous trust considerations linked to the privacy and security of the data collected by the workstation 142 .
Figure 5 Intelligent workstation with embedded sensors to learn and adapt indoor environment based on user preferences.
…”
Section: Research and Practice In Hbimentioning
confidence: 99%